New radiocarbon dates from the Edomite highlands and the hydraulic systems of southern Jordan - Tebes, Juan Manuel (2020)
Fil: Tebes, Juan Manuel. Pontificia Universidad Católica Argentina. Facultad de Ciencias Sociales. Centro de Estudios de Historia del Antiguo Oriente; Argentina